The island of dr. moreau eaudiobook - Wells, H.G (Recorded Books Inc., 1996)
Written by H.G. Wells, the great visionary author, this legendary novel is both timeless and thought provoking. Listeners will thrill to this chilling masterpiece as man boldly takes evolution into his own hands for the first time. Dr. Moreau, a scientist expelled from his homeland for his cruel experiments, continues his transplantations on a small South Pacific island, creating hideous creatures with manlike intelligence. When the island' s human/beasts revolt, the true consequences of his genetic meddling emerge. This stunning novel introduces listeners to the potential perils and gains of scientific discovery. H.G. Wells, author of the science fiction novels The War of the Worlds, The Invisible Man, and The Island of Dr. Moreau, remains the standard by which modern fantasy authors are judged.